Playing God [videorecording (DVD)] - Brignac, Scott; Kasulka, Hannah; Benward, Luke; McKean, Michael (Vertical, 2021)
A pair of con artists recruit their longtime mentor to 'play' God in order to scam a grieving billionaire.